RAZLIKE U MOTORIČKIM SPOSOBNOSTIMA BOKSERA I NESPORTISTA - Benin Murić; Izet Kahrović; Oliver Radenković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This research was conducted with the aim to define differences in motor abilities and morphological characteristics between judists and non/athletes of the same age. Sample encompassed 120 subjects having 60 students non/athletes and 60 students actively engaged in sports. For the evaluation of motor abilities there were conducted 12 measuring instruments. Testing of the posted hypotheses was performed on the basis of statistical data. The obtained results of this research in motor area have shown that there is statistically significant difference between selected boxsers and students not going in for box. This difference is defined by significantly better values and results in motor tests performed by the selected boxers.